Measures of human capital and nonlinearities in economic growth - Kalaitzidakis, Pantelis; Mamuneas, Theofanis P.; Savvides, Andreas; Stengos, Thanasis (My University, 2001)
In this paper we study the relationship between human capital accumulation and economic growth using various measures of human capital frequently employed by researchers. We use semiparametric estimation techniques to uncover any nonlinearities that may exist. Using mean years of schooling measures of human capital we find a nonlinear effect on economic growth. There seem to be important differences in the growth effect of educational attainment by gender and level of education. Enrollment rates do not yield a nonlinear effect.
Keywords: Cross country growth regressions; Human capital; Semi-parametric additive linear model